Jurnal Penyuluhan: Kapasitas Petani Kakao Bekas Penambang Batu Bara di Kota Sawahlunto - Delki Utama Asta, Aida Vitayala S Hubeis, Anna Fatchiya (PPs ILMU PENYULUHAN PEMBANGUNAN IPB, 2015)
The study aims to: (1) analyze the capacity of cocoa farmers ex-coalmining in Sawahlunto and (2) analyze factors that corrrelated with the capacity of cocoa farmers ex-coalmining in Sawahlunto. This research used survey method and was conducted in Sawahlunto City, West Sumatera on Desember 2014-February 2015.